Sifat Mekanis Beton Normal dengan Campuran Tepung Marmer - Kushartomo, Widodo; Sari, Dewi Permata (Department of Civil Engineering, Diponegoro University, 2018)
This study is describe about the mechanical properties of normal concrete by adding of marble flour based on the mixed plan made. The compressive strength of the planned test object fc '20.0 and fc' 30.0 MPa was prepared by using the ACI method. The addition of marble flour in a concrete mixture varies from 0%, 5%, 10%, 15%, 20% and 25% to the weight of the cement used. Concrete test specimens were made in the form of cylinders 15.0 cm in diameter, 30.0 cm in height and made in the form of concrete beams measuring 15.0 cm x 15.0 cm x 75.0 cm, the type of mechanical testing performed in the form of compressive strength tests on cylindrical specimen, split tensile strength test on cylindrical specimen and flexure test on beam specimen. Curing is done by immersion technique at 25ºC and the test is done when the concrete is 28 days old. The test results show that the addition of marble flour to the normal concrete mixture can increase its mechanical properties by 26% for compressive strength, 24% for split tensile strength, and 17% for flexural strength.